(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
Using official annual data from the National Statistics Committee of Uzbekistan (2010–2025), this paper tracks ICT employment across all economic sectors and regions. ICT employment more than doubled – from 53,100 to 108,800 workers – growing at roughly 2.8% per year before the 2017 reform era and accelerating to 6.8% afterwards. Despite this, the sector still accounts for under 1% of total employment, remains concentrated in Tashkent, and would need to grow at over 22% annually to hit the government’s target of 300,000 IT jobs by 2030. We argue this reflects an early but genuine structural shift, constrained by skills gaps and geographic inequality, and offer five focused policy recommendations.